2015
DOI: 10.1371/journal.pone.0135014
|View full text |Cite
|
Sign up to set email alerts
|

Macro-Particle Charcoal C Content following Prescribed Burning in a Mixed-Conifer Forest, Sierra Nevada, California

Abstract: Fire suppression and changing climate have resulted in increased large wildfire frequency and severity in the western United States, causing carbon cycle impacts. Forest thinning and prescribed burning reduce high-severity fire risk, but require removal of biomass and emissions of carbon from burning. During each fire a fraction of the burning vegetation and soil organic matter is converted into charcoal, a relatively stable carbon form. We sought to quantify the effects of pre-fire fuel load and type on charc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Because our fuels data were collected for the plot scale, we do not have spatially explicit relationships between downed wood biomass and C or PyC CTR loss from soil at the scale of soil sample locations. However, Weichman et al (2015) found no correlation between PyC stock and distance (up to 60 cm) from charred logs 12 years after a prescribed fire in mixed conifer forest. They suggest that charcoal shed from large-diameter downed wood either takes more than a decade to slough off the bark, or is rapidly redistributed away from the logs.…”
Section: Wildfire Impacts On Organic Horizon and Mineral Soil C And Pycmentioning
confidence: 73%
See 1 more Smart Citation
“…Because our fuels data were collected for the plot scale, we do not have spatially explicit relationships between downed wood biomass and C or PyC CTR loss from soil at the scale of soil sample locations. However, Weichman et al (2015) found no correlation between PyC stock and distance (up to 60 cm) from charred logs 12 years after a prescribed fire in mixed conifer forest. They suggest that charcoal shed from large-diameter downed wood either takes more than a decade to slough off the bark, or is rapidly redistributed away from the logs.…”
Section: Wildfire Impacts On Organic Horizon and Mineral Soil C And Pycmentioning
confidence: 73%
“…For example, a study conducted 4-5 years after fire in an Oregon mixed-conifer forest showed that low-severity areas were a net sink of C even though they had only partially recovered the lost C, whereas high-severity areas were still a C source because of dead wood decomposition (Meigs et al, 2009). Weichman et al (2015) found that 50% of emitted C was recovered 10 years after a prescribed burn in a California mixed-conifer forest, whereas Eskelson et al (2016) reported significant losses of live wood C in low-and moderate-severity areas, but no change in highseverity areas, over 6 years post-fire for 130 Forest Inventory and Analysis plots in the same state. Therefore, in fire-prone forests, increases in fire severity have potential to increase short-term C losses via fire emissions (including emissions from otherwise longer-lived C pools such as dead wood and mineral soil C) as well as decrease longer-term C storage by slowing the rate of postfire forest recovery (Pan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that PyC has widely been recognized as a highly chemically stable form of ecosystem C that is formed in all biomass burning events and is of great importance to global C cycle, to date there has been limited effort to quantify forest fire generated PyC and in particular that affiliated with Rx fire events in forest ecosystems (Alexis et al, 2012;Pingree et al, 2012;Wiechmann et al, 2015). In addition to wildfire events that commonly occur as a result of local climatic conditions at the seasonally dry forest ecosystems of the Rocky Mountain West (Agee, 1996), Rx fires are applied widely as a forest management practice throughout the region to reduce surface fuel loading and restore the historical fire regime (Ryan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Within this continuum, charcoal comprises coarse particles (mmcm) that retain the physical and chemical properties allowing to identify its biomass source (Bird and Ascough, 2012;Knicker et al, 2008;Scott, 2010). The aromatic structure gives charcoal an inherent increased resistance to biotic and abiotic degradation (Eckmeier et al, 2007;Wiechmann et al, 2015), which is further increased once the charcoal is buried in soil, due to enhanced physical protection, to an extent that charcoal is a common source of paleoenvironmetal and archaeological proxy data (Ascough et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, charcoal is a heterogeneous material (Bird and Ascough, 2012;Pyle et al, 2015), whose variability is mostly due to differences in burning conditions (in terms of temperature, duration, flaming or smouldering conditions, oxygen availability et cetera) and source materials (e.g. woody or grass vegetation, leaves or branches, conifers or broadleaves) (Bodí et al, 2014;Knicker et al, 2008;Merino et al, 2015;Santín et al, 2012;Wiechmann et al, 2015) and their interactive effect (Hatton et al, 2016). Therefore, charcoal heterogeneity is particularly high in fire affected natural forest ecosystems, due to an often wide diversity of species, fuel types, structure and density, combined with a high spatial and temporal variability in fire behaviour (temperature, flame residence time, oxygen availability) in a given fire (Pyle et al, 2015;Santín et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%